The International and Political Journal: Tribal Democracy in Mauritania - Jubeir, Dr.Ali Saadi Abdel Zahra; Al-Saadi, Lecturer Rahim Saddam Jabr (The International and Political Journal, 2024)
The affairs of the tribe are handled by its chief, and the Council (Dissolution and Contract) assists him in assuming the functions assigned to the tribe. The source of authority in the tribal system is the customs, traditions, and laws applied in the tribe, and not the tribal chief, who may be revolted if he loses justice. After independence from the French colonialists, the Mauritanian state tried to target the traditional tribal structure and replace it with loyalty to the state, but it was unable to do so. Rather, the role of the tribe increased after the adoption of party pluralism in 1991, due to the ruling elite resorting to the tribe to obtain more electoral votes. Thus, the tribe became the one running the state and not the other way around. That is why, the Mauritanian democracy is called a tribal one.